47th AIAA Fluid Dynamics Conference 2017
DOI: 10.2514/6.2017-3632
|View full text |Cite
|
Sign up to set email alerts
|

Measurements in the Boeing/AFOSR Mach-6 Quiet Tunnel on Hypersonic Boundary-Layer Transition

Abstract: This paper presents results from four different research projects currently ongoing at Purdue University. (1) Different criteria for detecting the edge of the boundary layer were investigated on the flared cone geometry. It was determined that a method based on the total enthalpy profile would be used for future edge-detection computations on the flared cone geometry. A Rod Insertion Method (RIM) roughness insert was measured using a Zygo ZeGage optical profiler. Experimental results with a single RIM insert a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…For comparison, the other probes range from being a wire sensor 5-µm in diameter to a maximum of 6.35 mm in diameter for the PCB probe. Previous computational 34 and experimental 35 studies have shown that the geometry of pitot probes used can affect the measurement of freestream disturbances. It is possible that this peak is a result of an unsteady bow shock ahead of the larger probe body.…”
Section: B Heat Transfer Fluctuationsmentioning
confidence: 99%
“…For comparison, the other probes range from being a wire sensor 5-µm in diameter to a maximum of 6.35 mm in diameter for the PCB probe. Previous computational 34 and experimental 35 studies have shown that the geometry of pitot probes used can affect the measurement of freestream disturbances. It is possible that this peak is a result of an unsteady bow shock ahead of the larger probe body.…”
Section: B Heat Transfer Fluctuationsmentioning
confidence: 99%